The virtuous psychiatrist character ethics in psychiatric practice - Radden, Jennifer; Sadler, John Z., 1953- (New York ; Oxford : Oxford University Press, 2010)
The context for this interdisciplinary work by a philosopher and a clinician is the psychiatric care provided to those with severe mental disorders. Such a setting makes distinctive moral demands on the very character of the practitioner, it is shown calling for special virtues and greater virtue than many other practice settings.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Psychiatric ethics; Psychiatry -- Moral and ethical aspects; Virtues